The Case for Multimodal Assessment: Reflections from an Italian Pilot Study - White, Jonathan Paul (GILE Journal of Skills Development, 2025)
Higher education institutions are increasingly exploring multimodal pedagogies, yet assessment still reflects the past more than the present. This short contribution explores the readiness of students and teachers for digital multimodal composing (DMC) assessment, synthesising themes from a preliminary study at an Italian university with perspectives from extant research. The project functions as a proof of concept, surfacing both enthusiasm and resistance in a context historically dominated by written and oral exams. The article proposes four guiding questions related to accessibility, transferable skills, instruction, and assessment criteria, which can help educators reflect on how multimodal assessment can be effectively designed and implemented.